GESTÃO DA PÓS-GRADUAÇÃO NA UNIVERSIDADE FEDERAL FLUMINENSE: UM ESTUDO DE CASO - Oliveira, Rosana Therezinha Queiroz de (2007)
Two government agencies have been outstanding in their support of Post-Graduate programs stricto sensu in Brazil: Capes at the program level, and the CNPq in its support of teachers and researchers. In the [attempt/desire] to reach the standards of quality set by these two government agencies, Universities, Post-Graduate Programs and researchers are developing strategies and putting into effect activities to help them achieve excellence in their respective areas of knowledge. This paper is meant to add to an improved understanding of what is being implemented in this environment through a case study relating the stricto sensu programs of the Federal University of Fluminense (UFF), to Concepts 6 and 7 of the most recent Capes evaluation. To maintain the consistency of the study, a bibliographic survey, combined with a documentary search is used and the data compiled using transverse analysis. The history of the institutionalization of post-graduate education and research is used to put this issue in context, to reach the point where we are in Brazil today. Next the paper provides an analysis of the realization of the process of evaluation of the stricto sensu programs by Capes. In the case study analysis, the approach continues by presenting an examination of two programs at UFF, UFF, showing how the criteria are followed and the indicators of excellence are reached by means of observation in loco. This led the study to its conclusions about the programs that are the focus of this study, identifying three factors that demonstrate the different levels of importance for the evaluation by Capes: the question of hierarchy; the different use of the indicators that reflect quality and quantity, and the specifics that exist in each area of knowledge. The case study shows how UFF adheres to the programs over these three interacting evaluating factors, which allows us to determine if the answer to the question asked was reached and with this the objectives of the study were achieved